2015
DOI: 10.1037/neu0000154
|View full text |Cite
|
Sign up to set email alerts
|

Negative social interactions and risk of mild cognitive impairment in old age.

Abstract: Objective To test the hypothesis that negative social interaction in old age is associated with increased risk of mild cognitive impairment and rate of cognitive decline. Methods Participants are 529 older people without cognitive impairment at study onset. They completed annual evaluations that included assessment of negative social interaction frequency in the previous month (e.g., unsympathetic behavior, rejection), cognitive testing, and clinical classification of mild cognitive impairment. Results Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 66 publications
4
52
0
3
Order By: Relevance
“…This was consistent with previous study findings (32,33). It was suggested that people who felt lonely were more vulnerable to some dangerous age-related neuropathological effects, because of their compromised neural system about memory and cognition which were deepened by loneliness (33). Furthermore, the mean age of the study population was 68.8 years old; and most of them (76.1%) were not working, and they had to stay at home while their children went out to work.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This was consistent with previous study findings (32,33). It was suggested that people who felt lonely were more vulnerable to some dangerous age-related neuropathological effects, because of their compromised neural system about memory and cognition which were deepened by loneliness (33). Furthermore, the mean age of the study population was 68.8 years old; and most of them (76.1%) were not working, and they had to stay at home while their children went out to work.…”
Section: Discussionsupporting
confidence: 94%
“…Those who were feeling lonely were 1.2 times greater odds to have MCI compared to their counterparts. This was consistent with previous study findings (32,33). It was suggested that people who felt lonely were more vulnerable to some dangerous age-related neuropathological effects, because of their compromised neural system about memory and cognition which were deepened by loneliness (33).…”
Section: Discussionsupporting
confidence: 92%
“…11,16,4648 Social disengagement, manifesting as low numbers of social ties, contacts, and group activities, has been associated with cognitive decline in population-based studies of older people, even in those individuals with relatively high baseline cognitive and functional status. 46,47 Many studies have also found independent effects on long-term cognition for more qualitative social and socioemotional constructs such as emotional support, 47 negative social interactions, 49 and loneliness. 6,9 Within this body of work, loneliness has been viewed as a marker of psychosocial stress, closely related to depression, 50 bereavement, 15 and other experiences of social disconnection, 51,52 with downstream effects on neural networks and systemic health, mediated by stress-related 5355 and inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisas (Fankhauser et al, 2015;Wilson et al, 2015) & Nilsson, 2015). No entanto, as relações sociais e a rede social são variáveis complexas, quando se considera a influência delas na proteção potencial contra a doença de Alzheimer e outros tipos de demência.…”
Section: Resultsunclassified
“…Além disso, os sintomas depressivos e engajamento social têm sido associados com risco de comprometimento cognitivo leve (CCL) e relacionados com pontuação negativa de interação social (Wilson et al, 2015). Nesse mesmo estudo detectou-se que as interações sociais negativas crônicas podem ser um fator de Clarke et al (2015) utilizaram dados do Chicago Health and Aging Project, um estudo longitudinal e prospectivo o qual examinaram o papel dos fatores individuais e de vizinhança na trajetória da função cognitiva em idosos.…”
Section: Resultsunclassified